Formation and Structure of Sclerotia and the Occurenceof Microconidia of Sclerotinia Sclerotiorum (Lib.) De Bary - Buddy Dani Kosasih (Journal of Mathematical and Fundamental Sciences, 1976)
Abstract. The development of sclerotia, structure and microconidia of Sclerotinia Sclerotiorum are described. Sclerotial initials are formed by hyphal strands which branched dichotomously to give a small knot and bound the hyphae together and then became solid masses which were spherical to irregular in shape. The mature sclerotium are blackand consists of three distinct regions, the outermost layer is a rind, within the rind is a cortex and the centre of the sclerotium is a medulla. Microconidia are readily produced in cultures of the fungus but no evidence was found of microconidial clusters forming within the sclerotium.Ringkasan. Pertumbuhan sklerotia, struktur serta pembentukan mikrokonidia pada Sclerotinia sclerotiorum, suatu jamur penyebab penyakit tumbuhan, telah dipelajari. Bakal sklerotia dibentuk di ujung-ujung hifae yang bercabang secara "dichotam", kemudian membentuk suatu bulatan kecil dan akhirnya menjadi massa yang padat, berbentuk bular atau tidak beraturan. Sklerotia yang sudah tua berwarna hitam dan terdiri dari tiga bagian yaitu bagian luar sekali disebut "rind", kemudian diikuti bagian "cortex" dan bagian tengah sekali adalah "medulla". Dalam perbenihan, jamur tersebut dapat membentuk mikrokonidia, tetapi pembentukan ini dalam sklerotia tidak terdapat.